The economics of transition : developing and reforming emerging economies - Iwasaki, Ichiro (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"In the last three decades since the fall of the Berlin Wall, there is a vast amount of study looking at transforming the planned economy to a market economy from both theoretical and empirical aspects. This book provides an overview and insight into transition economies in the recent decades and looks at key economics topics from the so-called "transition strategy debate" to the environmental reform. The book also includes an analytical review and meta-analysis of the existing literature. By integrating theoretical discussions and synthesizing empirical findings in a systematic manner, this book may help to enlighten the debate on time speed and policy sequence of economic transition. The book will appeal to particularly researchers, policy makers, other practitioners, and under- and post-graduate students who are interested in transition economies in Eastern Europe, former Soviet Union, Southeast Asia, and China. It aims to be read as an advanced reader"--
OCLC-licensed vendor bibliographic record.
Keywords: Developing countries -- Economic conditions -- 20th century; Developing countries -- Economic conditions -- 21st century; Economic development -- Developing countries -- History -- 20th century; Economic development -- Developing countries -- History -- 21st century; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Development / General